Clean and dirty energy cultures in the European Union - Rosicki, Remigiusz (WNPiD UAM, 2017)
The object of analysis in the text are “energy cultures” in the member states of the European Union (EU-28). The text attempts to verify the legitimacy of the statements pointing to the possibility of grouping the European Union member states according to a special kind of energy use practices. In order to elaborate the research problem the text features the following research questions: (1) Is it legitimate to claim that within the EU-28 there are special “energy cultures”?, (2) If the claim of the existence of special “energy cultures” is legitimate, what features determine the division among the EU-28 countries? These questions should be associated with the intention to establish the existence of the division of the EU-28 states into “clean” and “dirty” energy cultures. Such a division can be substantiated by individual features of the EU-28 member states, related to energy production, consumption and conversion, e.g. GHG emissions and the commitment to the coal sector. For the adopted premises to be verified, the analysis employed one of the agglomerative methods (i.e. the Ward’s method) and one of the methods for optimising a given group of objects (i.e. the k-means method). Besides, with the aid of individual tests, the differences in the level of parameters between the isolated clusters of countries were analysed. Furthermore, with the aid of the principal component method groups of independent factors were isolated, and the scope of essential differences in the level of the isolated factors between the grouped EU-28 member states was determined.
It is next to impossible to present an exhaustive analysis of the comprehension of the concept of culture, which results from the fact that it is used in a variety of spheres and branches of science. The definitions of the concept of “culture” that are usually mentioned are of a postulative (i.e. operative) character, but – despite the multi-layered discourse on the subject – it is possible to point to several main directions or elements that matter. In the first place, attention should be drawn to the approaches to culture as a process and form of resource transformation, as well as the impact of the transformation on reality. Subsequently, culture can be approached as a special kind of the sphere of social awareness (Cf. Kłosowska, 1969; Kłosowska 1972; Keesing, 1974, pp. 73-94; Nowicka, 1991, pp. 55-88; Burszta, 1998, pp. 35-57; Gajda, 2008, pp. 17-60; Strinati, 1998, pp. 15-49). Hence, culture can be understood as all of the tangible and intangible effects of human activity. Noteworthily, such aspects of the phenomenon of culture as normativity, functionality, structurality, adaptiveness can be pointed out. As regards the research into the energy culture, the two above-mentioned ways of approaching culture come to be reflected in the methods and techniques of the research into the issue. The first direction of research into energy culture is related to the way resources are transformed. In the case in question, it is a presentation of the characteristic features connected with production of “energy” sensu lato. Most frequently, this approach is expressed in the presentation of analyses concerned with: (1) energy production (and its diversification), (2) energy consumption (and its diversification), (3) import dependence, (4) development of new energy technologies, (5) energy use-related pollution. The other direction of research presents analyses concerned with a particular kind of awareness on the part of individuals and social groups, which can be exemplified by research into environmental awareness within the context of energy generation problems. As regards the analyses concerned with a special kind of energy production, consumption and conversion practices, there are both qualitative and quantitative research projects. The qualitative research is usually based on the presentation of descriptive analyses that synthesise and generalise energy cultures. Such research results in synthetic “models” exposing dominant features of energy structures in individual states and/or groups of states (Łucki, Misiak, 2010, pp. 47-50, 72-78; Frączek, 2014, pp. 443-449). The quantitative research concerned with energy production and consumption practices can be exemplified by analyses conducted on the basis of a variety of classification algorithms. This kind of research will include the studies involving the Ward’s method and the k-means method (Tapio et al., 2007, pp. 433-451; Pach-Gurgul, 2012, pp. 160-202; Pach-Gurgul, Soliński, 2013, pp. 17-30; Frączek, Majka, 2015, pp. 215-223; Rosicki, 2016, pp. 225-237). As regards the second current of research into energy cultures, that is the ones concerned with the research into awareness, environment-friendly behaviour and attitudes towards energy saving, quantitative research based on survey techniques and qualitative research based on various forms of open interviews are the most representative ones. The scientific research within this scope concerns such issues as the construction of the “model” of behaviour patterns and habits (frequently behaviour patterns among individual energy users). Furthermore, this current also features the results of the survey research targeted at a specified statistical sample selected from the population with a view to establishing the awareness, behaviour and habits concerned with the use of energy. With this goal in mind, in-depth analyses are conducted as regards the influence of socio-demographic and psychological factors on awareness, behaviour patterns and practices among energy users (Cf. Stern, Gardner, 1981, pp. 329-342 ; van Raaij, Verhallen, 1981, pp. 253-257; van Raaij, Verhallen, 1983a, pp. 39-63; van Raaij, Verhallen, 1983b, pp. 85-106; Stern, 2000, pp. 407-424; Lindén, Carlsson-Kanyama, Eriksson, 2006, pp. 1918-1927; Papuziński, 2006, pp. 33-40; Tuszyńska, 2007, pp. 233-236; Hłobił, 2010, pp. 87-94; Frederiks, Stenner, Hobman, 2015, pp. 573-609). In the case of the research presented in the text, a statistical analysis of the energy cultures in the European Union member states will be employed. Such an approach to the issues does not obviate the need to present the content of the concept of “clean” and “dirty” energy cultures. If we assume that an energy culture is a special kind of energy production, consumption and conversion practices, then belonging to either “clean” or “dirty” energy cultures will be determined by the values of parameters of individual indexes characterised by individual diagnostic features of energy cultures. The diagnostic features characteristic of the “clean” or “dirty” energy use have been recognised as: (1) emission performance, (2) energy production structure, (3) energy efficiency, (4) transport fuel structure. For instance, the clean energy culture will be determined by low GHG emissions, a considerable share of renewable sources in the energy production structure, a high level of energy efficiency, as well as a considerable share of renewable sources in transport fuels. The “dirty” energy cultures will be marked by opposite tendencies.
Keywords: energy policy; polityka energetyczna; energy security; bezpieczeństwo energetyczne; energy cultures; kultury energetyczne; clean energy cultures; czyste kultury energetyczne; dirty energy cultures; brudne kultury energetyczne; energy culture indexes; wskaźniki kultur energetycznych; European Union; Unia Europejska